The relationship between perceived interpersonal behaviors of coaches and sport confidence in Iranian senior free style wrestlers participating in a national training camp - Tavakolian, A.; Abolalizadeh, J.; Abolalizadeh, A. A.; Sohrabi, M. (International Journal of Wrestling Science, 2013)
Purpose: Most athletes, coaches, and sport psychology consultants strongly believe that confidence is a crucial psychological requisite for success in sport, and enhancing self-confidence is often a crucial consideration for all athletes (1). Based on the multidimensional sport-confidence model (Vealey & Chase, 2008), Coaches` behaviors, such as their interpersonal behaviors, may greatly influence athletes` self-confidence (2). Previous research has shown that the coaches` behaviors can be a significant social factor that influences athletes` affect cognition and behaviors (3). Accordingly the purpose of this research was to determine the relationship between perceived interpersonal behaviors of coaches and sport confidence in Iranian senior free style wrestlers participated in national training camp. Methods: Participants were 30 Iranian senior free style wrestlers participating in a national training camp, who completed The Sport-Confidence Inventory (SCI) Vealey & Knight (2002) and Interpersonal Behavior Scale for Sport (IBS-S) Pelletier et al. (2008). The content validity of these instruments was confirmed by experts and the internal consistency of the SCI and IBS-S scale proved to be 0.87 and 0.80 respectively in a pilot study. The data were analyzed by employing Pearson correlation and stepwise regression tests. Results: The results in Table 1 showed that there is a positive relationship between autonomy-supportive behaviors and Sport-confidence about physical skills and training (p=0.034, r=0.388 positive relationship between Social support behaviors and Sport-confidence about cognitive efficiency (p=0.007, r=0.485) and positive relationship between positive feedback behaviors and Sport-confidence about resilience (p=040.0, r=0.508).